THE EFFECTIVENESS OF NURSE-LED INTERVENTIONS IN IMPROVING WOUND CARE OUTCOMES - Safia Lbrahim Alfif, Adel Hamad Alsalman, Hussin Saeed Mohammed Alqhtani, Abdulrahman Yahya Sahli, Nader Hammad Aldawsari, Hassan Abdoh Sawadi, Bader Hamad Abdullah Alhamdani, Ahmed Abdullah Alhuwaykan, Fala Fahad Alkwairan, ,; Maha Matar Suwayhid Alenezi, Omar Abdalaziz Gaib Alzahrani, Kareman. Abdulftah . Abdulati . Aman, Anoudaaligaiday Alenazi, Naemih Marzuq Alhusayni, Anwar Mohammed Alruwaili, Salwa Abdullah Aldosugi, (Chelonian Research Foundation, 2022)
Chronic wounds have a detrimental impact on individuals' quality of life and impose a significant financial burden on the Australian healthcare system. Insufficient understanding of the importance of chronic wounds results in a scarcity of resources for delivering evidence-based treatment. Nurses in the community are responsible for managing the majority of chronic wounds. To improve future practice, it is necessary to have a deeper knowledge of the present models of care. To conduct a comprehensive analysis of the existing literature about the results and satisfaction levels of individuals who get treatment for long-lasting wounds from nurses in community settings. The results indicate that treatment delivered by nurses was economically efficient, showed significant client satisfaction, and led to enhanced wound healing and decreased pain levels. Providing treatment supervised by nurses is a beneficial experience for those with chronic wounds and results in improved outcomes. The results indicated a want for further client instruction and specialized training for healthcare professionals who oversee persistent wounds. Keywords: nurse, wound care, medical facilities, review, nursing intervention